Indirect selection for the size of seedling in vitro cultivation of passion fruit (Passiflora Giberti N. E. Brown) (Research, Society and Development, 2020)
It is known that the use of larger seedlings ensures greater precocity in the orchard. However, for plant tissue culture, only the seedling size is no guarantee of quality material for in vitro propagation. In this sense, the objective of this work was to use the trail analysis to identify which or which variables evaluated during the in vitro conservation process had the greatest direct influence on the number of viable gems available for further propagation. The data used in this work were from an in vitro conservation experiment of passion fruit plants of the species Passiflora giberti N. E. Brown. The variables evaluated were: length, fresh weight, dry weight, seedling vigor, and a number of viable buds. Simple correlation, partial correlation, and trail analysis were performed to describe the causal relationships between them. This analysis methodology showed that the vigor of the plant is the most correlated variable and also the one that has the greatest direct effect on the number of viable buds available.